Giant recurrent retroperitoneal liposarcoma initially presenting as inguinal hernia : review of literature - Leão, Pedro (2012)
Pedro Leão, Sónia Vilaça, Mário Oliveira and Joaquim Falcão have helped in the acquisition of data. Pedro Leão wrote the manuscript